A Review of SiC Wafers In-Line Detection Method in Power Device Fabrication. Issue 2 (March 2020) - Li, Ling; Li, Jialin; Wu, Hao; Liu, Rui; Zhang, Hongdan; Tian, Liang; Zhu, Tao; Jiao, Qianqian; Jiang, Chunyan; Wu, Junmin; Pan, Yan
Abstract: Silicon carbide (SiC) has outstanding advantages such as wide band gap, high electron saturation drift speed, high thermal conductivity, high voltage and high temperature resistance. It is particularly suitable for making high-power devices. The in-line detection of wafers in the manufacturing process of SiC devices can reflect the quality of incoming materials and process quality. It is a very important part of the manufacturing process. SiC wafer's in-line inspections involves characterization of the epilayer thickness, surface defects and contamination, wafer warping, dielectric and metal film thickness, etching morphology, etc. Various test methods are compared and discussed in this paper and suggestions are given on detection method selection.